Capacitação de profissionais de enfermagem ingressantes: recurso estratégico para a manutenção da qualidade em ambiente hospitalar de alta rotatividade - Migowski, Sérgio Almeida (Universidade do Vale do Rio dos Sinos, 2011)
A considerable problem faced by hospital organizations is the high turnover of its nursing professionals. Specifically, at the Rio Grande do Sul State, which adopts a model of hospitals capable to assist, simultaneously, private customers and private plans customers, as well the the public health system provided by the Sistema Único de Saúde (Unique Health System), this feature leads to loss of valuable competences, with reflections on its organizational performance. The impact of this turnover in the reduction of the quality of the services provided has been object of studies in theliterature, but it doesn’t seem to be the case of a hospital located in the Rio Grande do Sul State. Despite its elevated turnover rates, it has maintained the certification that proves its quality through the Hospital Accreditation - Level 3. In the last years, its quality program has focused on incoming professionals training methods and continued education programs. The aim of this study is to analyze if the incoming nurses and nursing technicians training methods allow the maintenance of the quality of the nursing service provided. Questionnaires were administered to 23 nurses and 10 nursing technicians, from a total of 40 incoming professionals, on their perception of the acquisition of specific competences during the training. Simultaneously, 10 current nurses and five existing nursing technicians answered about their perceptions of the new nurses, while 14 existing nurses and 12 current technicians answered about the new nursing technicians. The variables analyzed in this questionnaire were knowledge (technical and prospective knowledge), skills (effective communication and integrated view of processes) and attitude (leadership). Data were inserted into the SPSS program, version 18, using the Non-Parametric Mann-Whitney Test. We performed a non-participant observation of 40 hours, an interview with the current professionals of the institution, the analysis of nursing care indicators and used a questionnaire administered by the training program coordination to the entrant professionals. There was similarity in the perceptions of incoming nurses and existing nursing professional that occurred the apprehension of the competence skills during the training, while incoming nursing technicians and existing professionals highlighted the competence attitude as the most noticed after the training. The care indicators showed significant reduction in the amounts of medication errors and of phlebitis and elevation in the patient fall rate, with marked improvement after the implementation of the current training method. The interviews with the incoming professionals indicate great satisfaction with the implanted method, coinciding with the interviews performed with the current professionals that highlight the attitude and the knowledge apprehended by the incoming professionals as differentials of the current method. The triangulation of these evidences suggests that the existing training method reflects in the elevation of the quality of the care service provided by the entering professionals, despite being placed inan environment of high turnover.
Keywords: Capacitação; Profissionais de enfermagem ingressantes; Qualidade; Rotatividade; Training; Incoming nursing professionals; Quality; Turnover; ACCNPQ::Ciências Sociais Aplicadas::Administração